Proinflammatory Cytokines (IL-1α, IL-6) and Hepatocyte Growth Factor in Patients with Alcoholic Liver Cirrhosis - Andrzej Prystupa; Paweł Kiciński; Jarosław Sak; Anna Boguszewska-Czubara; Anna Toruń-Jurkowska; Wojciech Załuska (Gastroenterology Research and Practice)
Background. The aim of the study was to assess the activity of interleukin-1α, interleukin-6, and hepatocyte growth factor protein (HGF) in serum of patients with alcoholic liver cirrhosis. Materials and Methods. Sixty patients with alcoholic liver cirrhosis treated in various hospitals were randomly enrolled. The stage of cirrhosis was assessed according to the Child-Turcotte-Pugh scoring system. The control group consisted of ten healthy persons without liver disease, who did not drink alcohol. Additionally, the group of alcoholics without liver cirrhosis was included in the study. The activity of interleukin-1α, interleukin-6, and HGF in blood plasma of patients and controls was measured using the sandwich enzyme immunoassay technique with commercially available quantitative ELISA test kits. Results. Higher concentrations of HGF protein were demonstrated in patients with Child class B and Child class C liver cirrhosis, compared to controls and alcoholics without liver cirrhosis. Moreover, significantly higher concentrations of HGF protein were found in patients with Child class C liver cirrhosis compared to patients with Child class A liver cirrhosis p<0.05. The concentrations of interleukin-1α in patients with Child class B and Child class C liver cirrhosis were significantly higher in comparison with controls. Significantly higher concentrations of interleukin-6 were demonstrated in Child class C, compared to Child class A.